IMPLEMENNTASI KONSEP KEAMANAN INSANI (HUMAN SECURITY) DI INDONESIA DALAM KONTEKS DAMAI DAN RESOLUSI KONFLIK - Rivaldo Noval Putra Santosa; Arief Budiarto; Yulian Azhari (Jurnal Education and Development, 2022)
Basically, the problem of human security is not identical with a mere military military threat. But this human threat can be interpreted as a threat that is transformed into a form of hunger and poverty that has an impact on the emergence of violence, either directly or indirectly. In Indonesia today, the trend of violence is more towards direct violence. Poverty and hunger are not the main causes of conflict. However, poverty and hunger are indirect causes of conflict.